Adherence to Mediterranean diet and dietary changes according to the fear of COVID-19 during the pandemic: a cross-sectional study. (8th May 2023) - Gumus, Damla; Topal, Gulsum Gizem; Sevim, Sumeyra; Kizil, Mevlude
Abstract: The coronavirus disease 2019 (COVID-19) has led to the implementation of restrictions to reduce transmission worldwide. The restrictions and measures have affected the psychological health and eating habits. The objective of the present study was to evaluate dietary habits, lifestyle changes, adherence to the Mediterranean diet (MD) and fear of COVID-19 in Turkey during the pandemic. A cross-sectional online survey of socio-demographic characteristics, anthropometric measurements, nutrition, physical activity and lifestyle habits was used for data collection. The fear of COVID-19 levels of the participants was determined by the fear of COVID-19 scale (FCV-19S). The Mediterranean Diet Adherence Screener (MEDAS) was used to evaluate participants' adherence to the MD. The differences between the FCV-19S and MEDAS according to gender were compared. Eight hundred and twenty subjects (76⋅6 % women and 28⋅4 % men) were evaluated within the study. The mean of MEDAS (ranged between 0 and 12) was 6⋅4 ± 2⋅1, and almost half of the participants moderately adhered to the MD. The mean of FCV-19S (ranged between 7 and 33) was 16⋅8 ± 5⋅7, while women's FCV-19S and MEDAS were significantly higher than men's ( P < 0⋅001). The consumption of sweetened cereals, grains, pasta, homemade bread and pastries of the respondents with high FCV-19S were higher than in those with low FCV-19S. High FCV-19S was also characterized by decreased take-away food and fast food consumption in approximately 40 % of the respondents ( P < 0⋅01). Similarly, women's fast food and take-away food consumption decreased more than men's ( P < 0⋅05). In conclusion, the respondents' food consumption and eating habits varied according to the fear of COVID-19.